Analysis of the PM2.5/PM10 Ratio in Three Urban Areas of Northeastern Romania - Liliana Drăgoi (Oniu); Marius-Mihai Cazacu; Iuliana-Gabriela Breabăn (Atmosphere)
The study was conducted in Suceava, Iasi, and Botosani, three geographically different cities in Romania with increasing PM10 concentrations, especially during the colder months. In order to assess the contributions of PM2.5 and PM10, the PM2.5/PM10 ratios were analyzed for the period 2019–2023. The results showed a downward trend in PM10 and PM2.5 concentrations, with a more significant decrease observed for PM2.5. However, although the annual PM2.5/PM10 ratios also decreased, their decrease did not follow the same pattern as the decrease in PM10 and PM2.5 concentrations. The annual PM2.5/PM10 ratios varied from 0.48 to 0.61 in Botosani, from 0.54 to 0.72 in Iasi and from 0.60 to 0.71 in Suceava. The seasonal analysis of the data showed that the highest ratios were observed in winter in Suceava, where wood is also used for residential heating. The frequency distribution of the ratios was examined for each season to determine the nature of the emissions: natural or anthropogenic. The analysis of the spatial variation of the PM2.5/PM10 ratio showed that the greatest differences occurred between Iasi and Botosani as indicated by a coefficient of divergence (COD) value of 0.236. Furthermore, the temperature was used to analyze its potential relationships in relation with the PM2.5/PM10 ratio.